A Model of Bystander Helping to Prevent Suicide: Examining and Extending the Theory of Planned Behavior - Banyard, Victoria (Journal of interpersonal violence, 2025)
Research documents alarmingly high suicidal behavior risk among adolescents and young adults in the United States. A related concern is similarly high rates of exposure to the self-directed violence (SDV) of others. The current study examined how components of the Theory of Planned Behavior explain factors related to helping social network members engaging in SDV. Baseline data (N = 4,982) from the longitudinal study, Project Lift Up, were analyzed cross-sectionally. Young people, ages 13 to 22, were recruited through social media platforms; sexual and gender minority youth were oversampled. Participants answered questions about exposure to other people’s SDV and measures of key constructs related to the Theory of Planned Behavior for helping reduce SDV including perceptions of what others think about helping and behavioral control. Three outcomes were assessed: Intent to help someone, proactive behavior to promote the other person’s mattering, and proactive behavior to prevent SDV. Measures showed adequate reliability and validity (Cronbach’s alphas above .70). Overall, regression analyses across the three outcomes partially supported the Theory of Planned Behavior. Attitudes and confidence explained variance in intent to help and proactive behavior outcomes, whereas intent and social norms showed more mixed associations with the three outcomes. While the Theory of Planned Behavior is useful to explain gatekeeper outcomes for suicide prevention, specific significant factors within the model vary by the specific outcome being examined. Further research to unpack nuances in gatekeeper behaviors is needed and may help design prevention strategies.